The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000104487
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Participation Level after Spouse’s First Stroke and Relationship to Burden and Depressive Symptoms

Abstract: Background: No comprehensive data are available on the impact of stroke on the spouse’s participation level. The purpose of this study was to document changes in participation level over time and explore associations between changes in participation level, burden and depressive symptoms for spouses of people who had had a first stroke. Methods: Participants were spouses recruited in the first 2 weeks after admission of individuals with a first stroke to acute care. Prestroke measures (T0) were collected at rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
(33 reference statements)
1
25
0
Order By: Relevance
“…The results indicate that a higher percentage of caregivers compared to their international counterparts experi enced strain (Visser Meiley et al 2005;Rochette et al 2007;Ilsei et al 2008). The caregiver strain was also higher than findings from the study by Kleineibst in 2007 in the same setting, but lower than findings from Wasserman et al (2009).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The results indicate that a higher percentage of caregivers compared to their international counterparts experi enced strain (Visser Meiley et al 2005;Rochette et al 2007;Ilsei et al 2008). The caregiver strain was also higher than findings from the study by Kleineibst in 2007 in the same setting, but lower than findings from Wasserman et al (2009).…”
Section: Discussionmentioning
confidence: 73%
“…This problem is echoed by studies from the United Kingdom (MacKenzie et al 2007) and Canada (Rochette et al 2007). Similarly Kleineibst (2007) and Wasserman et al (2009) mention finan cial challenges and changes in employ ment status as a major cause of caregiver strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other qualitative research has identified caregivers experience a reduction in social participation (Bulley, Shiels, Wilkie, & Salisbury, 2010) and loss of spontaneity and freedom (Bäckström & Sundin, 2009). Further, quantitative research suggests caregivers experiencing restrictions in working towards roles and goals of importance and value experience increased levels of depression (Grigorovich et al, 2016;Hwang, Rivas, Fremming, Rivas, & Crane, 2009;Mausbach et al, 2011;Rochette et al, 2007). Whilst some caregivers are able to re-engage with activities over time, those with higher levels of depression and caring for stroke survivors with greater illness severity are less likely to (Grigorovich et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of informal care to stroke survivors within the community can be challenging (Jaracz et al, 2015), and can be associated with significant emotional consequences including sleep difficulties (Rittman, Hinojosa, & Findley, 2009); loss of relationships with family and friends (Rochette, Desrosiers, Bravo, Tribble, & Bourget, 2007); withdrawal from social activities (Mausbach et al, 2011) and poor quality of life (Godwin, Ostwald, Cron, & Wasserman, 2013). Further, caregivers may experience poor physical health (Carretero, Garcés, Ródenas, & Sanjosé, 2009;Legg, Weir, Langhorne, Smith, & Stott, 2013) and reduced energy (Parag et al, 2008).…”
Section: Introductionmentioning
confidence: 99%